Ice fog in arctic during fram-ice fog project aviation and nowcasting applications - Gultepe, Ismail; Kuhn, Thomas; Pavolonis, Michael J.; Calvert, C.; Gurka, James J.; Heymsfield, Andrew J.; Liu, P.S.K.; Zhou, B.; Ware, Randolph H.; Ferrier, Brad Schoenberg; Milbrandt, Jason A.; Bernstein, Ben C. (Bulletin of the American Meteorological Society, 2014)
Increased understanding of ice fog microphysics can improve frost and ice fog prediction using forecast models and remote-sensing retrievals, thereby reducing potential hazards to aviation Validerad; 2014; 20140502 (andbra)